2014
DOI: 10.1038/leu.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of longitudinal whole-body magnetic resonance imaging in patients with smoldering multiple myeloma

Abstract: Previous studies demonstrated the relevance of focal lesions (FL) in whole-body magnetic resonance imaging (wb-MRI) at the initial workup of patients with smoldering multiple myeloma (SMM). The aim of this study was to assess the effects of longitudinal wb-MRIs on progression into multiple myeloma (MM). Sixty-three patients with SMM were analyzed who received at least two wb-MRIs for follow-up before progression into MM. Radiological progressive disease (MRI-PD) was defined as detection of new FL or increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 25 publications
2
57
1
2
Order By: Relevance
“…Radiological progression was defined by the appearance of new focal lesions or a new diffuse infiltration of previously unaffected regions. Progressive disease was identified in 31 patients (49%) and was associated with a 16.5-fold risk of progression into symptomatic MM compared with patients with a stable MRI [22] It is important to note that a focal lesion on MRI reflects the presence of tumor infiltration and is insufficient for the identification of an osteolytic process. Although the results on MRI are consistent between different groups and currently incorporated in the IMWG criteria of treatmentrequiring events, standardization in interpretation and reporting of MRI results is required in subsequent studies.…”
Section: Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological progression was defined by the appearance of new focal lesions or a new diffuse infiltration of previously unaffected regions. Progressive disease was identified in 31 patients (49%) and was associated with a 16.5-fold risk of progression into symptomatic MM compared with patients with a stable MRI [22] It is important to note that a focal lesion on MRI reflects the presence of tumor infiltration and is insufficient for the identification of an osteolytic process. Although the results on MRI are consistent between different groups and currently incorporated in the IMWG criteria of treatmentrequiring events, standardization in interpretation and reporting of MRI results is required in subsequent studies.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…A smaller study on 69 patients conducted by the Greek Myeloma Group indicated that the presence of $1 focal lesion in spine MRI was also associated with a short time to symptomatic disease (median 9 months vs. .5 years) [21]. The Heidelberg group retrospectively analyzed the outcome of 63 patients with SMM that received at least two MRIs during their follow-up [22]. Radiological progression was defined by the appearance of new focal lesions or a new diffuse infiltration of previously unaffected regions.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…74,75 In the study by Hillengass, 72 diff use MRI infi ltration was associated with a HR of 3·5 (p<0·001). A 2014 analysis 76 shows that the increase in number or size of focal lesions in follow-up MRI of patients with smouldering multiple myeloma has additional predictive value, including information on growth dynamics of the plasma cell tumours in bone marrow. Therefore, in patients with diff use infi ltration, solitary focal lesion, or in the presence of equivocal fi ndings, follow-up examinations in 3-6 months are strongly recommended.…”
Section: Mri With More Than One Focal Lesionmentioning
confidence: 99%
“…Other factors that predict progression to symptomatic disease include abnormal plasma cell phenotype in ≥95% of cells, high plasma cell proliferative rate, hypogammaglobulinemia, gene expression profile of the purified MM cells, abnormal free lightchain ratio, increasing M-protein, presence and development of MRI abnormalities, or peripheral blood circulating plasma cells [27,43,44,[49][50][51][52][53][54]. Also, hyperdiploidy, del(17p), t(4;14), and ampl(1q) are adverse prognostic factors in SMM, independent of tumor load [55,56] (Figure 1).…”
Section: Progression O F Smmmentioning
confidence: 99%